IMIA Accreditation of Health Informatics Programs - Hasman, A. (Yearbook of Medical Informatics, 2012)
To develop a procedure for accrediting health informatics programs.Development of a procedure for accreditation. Test of the accreditation procedure via a trial including four or five health informatics programs. A site visit committee consisting of three members evaluates the program based on a self-assessment report written by the program and the experiences and observations of the site visit committee during the site visit.A procedure for accreditation has been developed. The instructions for health informatics programs have been written and a checklist for the site visit committee members is available. In total six subjects are considered, each one consisting of one or more facets. Each facet is judged using its corresponding criterion. Five health informatics programs volunteered. One health informatics program in Finland has already been visited and a report has been produced by the site visit committee. The next site visits are in June and July 2012. The site visit in Finland showed that English summaries of master theses are not enough to get a first impression of the methods used in the thesis. A table of contents is also needed. This information then can be used to select theses written in a language other than English for discussion.The accreditation procedure document with instructions about writing the self-assessment report was very well structured and the instructions were clear according to the Finnish program. The site visit team could work well with the checklist. Self-assessment report model was very well structured and the instructions were clear.
Keywords: Accreditation; health informatics program; IMIA